2005
DOI: 10.1038/ng1562
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale structural variation of the human genome

Abstract: Inversions, deletions and insertions are important mediators of disease and disease susceptibility. We systematically compared the human genome reference sequence with a second genome (represented by fosmid paired-end sequences) to detect intermediate-sized structural variants >8 kb in length. We identified 297 sites of structural variation: 139 insertions, 102 deletions and 56 inversion breakpoints. Using combined literature, sequence and experimental analyses, we validated 112 of the structural variants, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
916
2
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 894 publications
(949 citation statements)
references
References 26 publications
24
916
2
7
Order By: Relevance
“…The proximal breakpoint is located in a long terminal repeat. Previous analysis of cytogenetic and submicroscopic inversion breakpoint regions show that repetitive elements, high sequence similarity to the opposite breakpoint, pseudogenes, gene desserts, segmental duplications and co-localization with fragile sites are over-represented [Feuk et al, 2005;Schmidt et al, 2005;Tuzun et al, 2005]. Although both breakpoints identified in our study are located within or adjacent to repeats, they showed no strong homologies to each other from sequence analysis.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The proximal breakpoint is located in a long terminal repeat. Previous analysis of cytogenetic and submicroscopic inversion breakpoint regions show that repetitive elements, high sequence similarity to the opposite breakpoint, pseudogenes, gene desserts, segmental duplications and co-localization with fragile sites are over-represented [Feuk et al, 2005;Schmidt et al, 2005;Tuzun et al, 2005]. Although both breakpoints identified in our study are located within or adjacent to repeats, they showed no strong homologies to each other from sequence analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…Detailed structural analysis of submicroscopic inversion variants indicates that they frequently origin from non-allelic homologous rearrangements between repeated and re-iterated sequences or duplicons [Shaw and Lupski, 2004;Bansal et al, 2007]. Recent progress in genomics indicates that most polymorphic inversions span minor regions down to a few kilobases of DNA [Feuk et al, 2005;Tuzun et al, 2005]. These inversions constitute a large part of the normal genomic variation among humans and may occur frequently as somatic events [Flores et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…When both ends of the DNA fragments that map to the reference genome show discordances in terms of size, this is an indication for deletion and insertion, whereas discordances in orientation suggests the presence of inversion. 101 The power of this method to detect inversions was first demonstrated in the study by Tuzun et al 102 by sequencing the fosmid paired-end sequences. The study successfully identified 56 inversion breakpoints.…”
Section: Copy Neutral Variations-inversions and Translocationsmentioning
confidence: 99%
“…17,18 In the last decade, hundreds of submicroscopic copy number variants (CNVs) and inversions have been described in the human genome. [19][20][21][22][23] This type of variants can contain millions of bases of DNA, encompassing entire genes and their regulatory regions. [19][20][21]23,24 CNVs in some genomic regions have no obvious phenotypic consequence, [19][20][21]23 whereas others might influence gene dosage leading to genetic diseases either alone or in combination with other genetic or environmental factors.…”
mentioning
confidence: 99%
“…[19][20][21][22][23] This type of variants can contain millions of bases of DNA, encompassing entire genes and their regulatory regions. [19][20][21]23,24 CNVs in some genomic regions have no obvious phenotypic consequence, [19][20][21]23 whereas others might influence gene dosage leading to genetic diseases either alone or in combination with other genetic or environmental factors. 25 Despite the identification of two genomic losses in the GNAS locus 26,27 reported in the Database of Genomic Variants (Center of Applied Genomics), to our knowledge,CNVs in the GNAS cluster were not studied in detail in patients with an AHO-like phenotype (including PPHP cases).…”
mentioning
confidence: 99%